2021
DOI: 10.1021/acs.accounts.1c00538
|View full text |Cite
|
Sign up to set email alerts
|

Local Charge Distributions, Electric Dipole Moments, and Local Electric Fields Influence Reactivity Patterns and Guide Regioselectivities in α-Ketoglutarate-Dependent Non-heme Iron Dioxygenases

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Non-heme iron dioxygenases catalyze vital processes for human health related to the biosynthesis of essential products and the biodegradation of toxic metabolites. Often the natural product biosyntheses by these non-heme iron dioxygenases is highly regio-and chemoselective, which are commonly assigned to tight substratebinding and positioning. However, recent high-level computational modeling has shown that substrate-binding and positioning is only part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 72 publications
1
70
0
Order By: Relevance
“… 26 , 41 Recent studies demonstrated that electrostatic perturbations could be a promising tool to modulate the rate and specificity of chemical reactions. 42 44 Computational methods thus have an important role in studying factors away from the active site that regulates the kinetics of individual steps in oxygenase catalysis. 28 , 29 , 45 …”
Section: Introductionmentioning
confidence: 99%
“… 26 , 41 Recent studies demonstrated that electrostatic perturbations could be a promising tool to modulate the rate and specificity of chemical reactions. 42 44 Computational methods thus have an important role in studying factors away from the active site that regulates the kinetics of individual steps in oxygenase catalysis. 28 , 29 , 45 …”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations demonstrated that ligand self-hydroxylation can be inhibited by adding external substrates, which can intercept the oxidant generated from dioxygen activation mediated by iron( ii )-α-hydroxy acid complex. 3,36,37 Although high-valent iron-oxo species have often been implicated as reactive intermediates in many oxygen activating enzymes, 1,4–15 there is also evidence for the oxidation capability of the iron-hydroperoxo species. 39–41,76 Thus, the two intermediates ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the oxidation capability of Fe II (OOH) and Fe IV (O)(OH) toward different external substrates Experimental investigations demonstrated that ligand selfhydroxylation can be inhibited by adding external substrates, which can intercept the oxidant generated from dioxygen activation mediated by iron(II)-α-hydroxy acid complex. 3,36,37 Although high-valent iron-oxo species have often been implicated as reactive intermediates in many oxygen activating enzymes, 1,[4][5][6][7][8][9][10][11][12][13][14][15] there is also evidence for the oxidation capability of the iron-hydroperoxo species. [39][40][41]76 Thus, the two intermediates (i.e., Fe II (OOH) (1) and Fe IV (O)(OH) ( 2)) involved in this dioxygen activation process described above may serve as the oxidants to complete the following oxidations.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sason Shaik et al ( Hirao et al, 2008 ; Gorin et al, 2012 ; Fried and Boxer, 2015 ; Li et al, 2015 ; Akamatsu et al, 2017 ; Che et al, 2018 ; Ciampi et al, 2018 ; He et al, 2018 ; Yu and Coote, 2019 ; Shaik et al, 2020 ; Shaik et al, 2004b ; Kraskov et al, 2021 ; Yu et al, 2021 ; Zhang et al, 2021 ; de Visser et al, 2022 ) found that oriented external electric fields (OEEFs) can be used as a new type of catalyst to catalyze reactions by stabilizing transition states through the interactions between OEEFs and the molecular dipole moments, and even can increase the selectivity of reactions through adjusting the direction of OEEFs. Through theoretical calculations, our group also found that the OEEFs can modulate the reaction process through the interactions with the dipole moment of the reaction molecules ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%